How child welfare professionals search for, access, and share information: Findings from the National child welfare information study. (November 2021) - Long, Michael; Bhattacharya, Sharika; Eaton, Elizabeth; Ferreras, Dannele; Zdawczyk, Christina; Leicht, Christine; Deakins, Brian; McGuire, Matthew
Highlights: Frontline workers are more likely than others to seek information from colleagues. Frontline workers prefer more visual formats for consuming information. Senior staff and legal professionals prefer more formal sources of information. A third of workers use mobile devices to regularly access job-related information. Mobile phones and social media may become key information channels in the future. Abstract: Child Welfare Information Gateway, with funding from the Children's Bureau of the U.S. Department of Health and Human Services, conducted the National Child Welfare Information Study between January and May 2019 to better understand how child welfare professionals search for, access, and share information. Topics covered in the survey included the general level of access to child welfare information, proactive searches for child welfare information, receiving child welfare information, sharing child welfare information, training, using mobile technology to access child welfare information, and using social media to access and share child welfare information. The results, based on 3, 313 responses, provide a valuable profile of how child welfare professionals interact with information as part of their work responsibilities. These findings will be useful to (1) technical assistance providers seeking to disseminate information to this audience, (2) people responsible for managing and directing child welfare organizations, and (3) other researchers who can use the data for additional exploration on these topics.